Impact of substage and histologic type in stage I ovarian carcinoma survival: a multicenter retrospective observational study. Issue 1 (14th September 2022) - Imterat, Majdi; Bizzarri, Nicolò; Fruscio, Robert; Perrone, Anna Myriam; Traut, Alexander; du Bois, Andreas; Rosati, Andrea; Ferrari, Debora; De Iaco, Pierandrea; Ataseven, Beyhan; Ergasti, Raffaella; Volontè, Silvia; et al.
Abstract : Objective: This international study aimed to investigate the impact of substage, histological type and other prognostic factors on long-term survival for stage I ovarian carcinoma. Methods: Our study was a retrospective multicenter cohort study that included patients with the International Federation of Gynecology and Obstetrics (FIGO) stage I (IA-IC3) ovarian carcinoma treated at four European referral centers in Germany and Italy. Using Kaplan-Meier survival curves we compared overall and disease-free survival between the different stage I groups. Results: A total of 1115 patients were included. Of these, 48.4% (n=540) were in stage IA, 6.6% (n=73) stage IB, and 45% (n=502) stage IC, of the latter substage IC1, 54% (n=271), substage IC2, 31.5% (n=158), and substage IC3, 14.5% (n=73). Five-year overall and disease-free survival rates for the entire cohort were 94% and 86%, respectively, with no difference between stage IA and IB. However, there was a significantly better overall and disease-free survival for stage IA as compared with stage IC (p=0.007 and p<0.001, respectively). Multivariate analysis revealed incomplete/fertility-sparing staging (HR 1.95; 95% CI 1.27 to 2.99, and HR 3.54; 95% CI 1.83 to 6.86, respectively), and stage IC (HR 2.47; 95% CI 1.63 to 3.75) as independent risk factors for inferior disease-free survival, while low-grade endometrioid (HR 0.42; 95% CI 0.25 to 0.72) and low-grade mucinous (HR 0.17; 95% CI 0.06 to 0.44) histology had superior disease-free survival. Considering overall survival, stage IC (HR 2.41; 95% CI 1.45 to 4.01) and older age (HR 2.41; 95% CI 1.46 to 3.95) were independent risk factors. Conclusion: Although stage I ovarian carcinoma exhibited excellent outcomes, the prognosis of patients with stage IA differs significantly compared with stage IC. Sub-optimal staging as an indicator for quality of care, and tumor biology defined by histology (low-grade endometrioid/mucinous) independently impact disease-free survival.